Homozygous deletion of exons 2–7 within TGFB3 gene in a child with severe Loeys‐Dietz syndrome and Marfan‐like features. Issue 5 (5th February 2020) - Mégarbané, André; Deepthi, Asha; Obeid, Marc; T. Al‐Ali, Mahmoud; Gambarini, Alicia; El‐Hayek, Stephany
Abstract: We describe a patient with palatal abnormalities—cleft palate and bifid uvula; distinctive facial features—long and triangular face, large ears and nose, thin lips and dental crowding; musculoskeletal abnormalities—severe scoliosis, joint laxity, long digits, flat feet, decreased muscle mass, and diminished muscle strength; and cardiac features—a dilatated ascending aorta at the level of Valsalva sinuses and a patent foramen ovale. Sequence analysis and deletion/duplication testing for a panel of genes involved in connective tissue disorders revealed the presence of a novel homozygous deletion of exons 2–7 in TGFB3 gene. Heterozygous pathogenic mutations in TGFB3 have been associated with Loeys‐Dietz syndrome 5 (LDS5) and Arrhythmogenic Right Ventricular Dysplasia type 1. Here, we report the first case of a homozygous TGFB3 variant associated with a severe LDS5 and Marfan‐like presentation.